Different coating type on copper substrate - Zulfadly Syazwan, Zolkhair (2013)
This thesis will deal with the effect of different coating types on solder joint strength, specifically on intermetallic compound (IMC). Coating is essential in printed circuit board application since it can protect the base material, which is Copper, from oxidation and degradation. However, the coating thickness will give different effect on solder jointstrength or life. Two types of surface finish have been used in this research which isElectroless Nickel and Electroless Nickel / Immersion Gold (ENIG). The purposes of thesurface finish are to provide a diffusion barrier, oxidation barrier, adhesion and solderablesurface on copper substrate. For this research, solder material that will be used is Sn-4Ag0.5Cu to form a solder joint. All samples were subjected to reflow soldering and then to the isothermal ageing at 150℃ with duration 250 hours and 500 hours. The IMCs werecharacterized using scanning electron microscopy and image analyser to investigate the thickness of IMC on solder joint at all samples. From the research, it was observed that the IMC growth is influenced by ageing duration where the thickness of IMC is increases with ageing.